Education on the benefits of choosing the right contraception for wus (women of childbearing age) to prevent unplanned pregnancy - Hasrida, Hasrida; Jusmawati, Jusmawati; Ulfa, Siti Maria (CV. Paperhome Indonesia, 2025)
Health education about types of contraceptives needs to be prioritized to support accessibility and diverse choices for Women of Childbearing Age. With adequate knowledge so that they can choose the right contraceptive according to their physical condition, it is useful for preventing unplanned pregnancies. Unplanned pregnancies can have serious impacts on both maternal and child health. Women who experience this tend to delay antenatal care, which can have an impact on the health of the baby and mother. In addition, it often leads to abortion, both spontaneous and planned, which increases the risk of medical complications and maternal death. This community service was carried out at PMB Umayyah on October 25, 2024. The target of this activity is Women of Childbearing Age who already have partners. The purpose of this community service is to increase the understanding of women of childbearing age regarding the concept of family planning and appropriate contraceptive methods and to empower and ensure that they can make the right decisions for their reproductive health. With the right education, women of childbearing age can understand and determine the right contraceptive choices to plan a pregnancy properly